A Natural Supramolecular Saponin Hydrogelator for Creation of Ultrastable and Thermostimulable Food‐Grade Foams. Issue 14 (5th June 2019) - Ma, Lulu; Li, Qing; Du, Zhenya; Su, Enyi; Liu, Xiao; Wan, Zhili; Yang, Xiaoquan
Abstract: A new class of food‐grade foams that are ultrastable, thermostimulable, and processable can be created simply by using the naturally occurring saponin glycyrrhizic acid (GA) as the sole stabilizer. The creation of this "superfoam" is based on the spatially controllable self‐assembly of supramolecular GA nanofibril hydrogelators at the air–water interface and in the continuous phase. The rapid adsorption of GA nanofibrils at the bubble surface, forming a multilayer interfacial network, combined with the formation of viscoelastic fibrillar hydrogel networks in the continuous phase, enables the foams having ultrastability over months or years without the water drainage induced phase separation, which have been evidenced using small angle X‐ray scattering and microscopy techniques. Such ultrastable foams can be rapidly destabilized on demand by heating, which induces the melting of the fibrillar networks. These thermoresponsive foams can be reversibly switched between stable and unstable by simply changing the temperature, based on the reversible gel–sol phase transition of the supramolecular hydrogel inside the foam. This is the first finding of a natural edible surfactant system that foams very well and can be used solely to make advanced foams with the qualities of simplicity, ultrastability, stimulability, and processability, which make them viable for many sustainable applications. Abstract : A new class of food‐grade foams that can be ultrastable, thermostimulable, and processable is created simply by using the naturally occurring saponin glycyrrhizic acid (GA) as the sole stabilizer. The creation of this "superfoam" is based on the spatially controllable self‐assembly of supramolecular GA nanofibrils at the air–water interface and in the continuous phase.